Teachers’ perspectives on motor learning with traditional game approach among early children - Banu Setyo Adi; Djoko Pekik Irianto; Yustinus Sukarmin (Jurnal Cakrawala Pendidikan, 2022)
Many traditional games originated from several local regions in Indonesia, especially Yogyakarta, may nurture learning in early childhood education. The study aims to explore the teachers’ perception in implementing, understanding, and adapting traditional games that could develop students’ motor skills in kindergarten. This research employed a quantitative descriptive approach with a questionnaire as its instrument, involving 35 kindergarten teachers The questionnaire was validated using an Aiken-V, The results showed that the teachers’ perspectives of traditional games were generally limited to a superficial understanding and were not yet deep in terms of its benefits to other learning aspects. The implementation of traditional games in learning was heterogeneous and merely based on the understanding of each teacher. To adapt traditional games, teachers relied on the curriculum sources and were reluctant to enrich themselves with other sources. It was concluded that the teachers have not been fully able to use the traditional games in physical motor learning in kindergarten. To integrate them in learning, teachers must deepen their understanding of traditional games and get to know the characteristics of early childreen.